A new tubal classification system for fertility prognosis after laparoscopic salpingostomy for tubal pregnancy. (August 2016) - Ding, Yan; Huang, Wen; Jiang, Hongyuan; Zhu, Jin
Abstract: Objective: To assess the objectivity and accuracy of a new system that predicts the pregnancy outcomes in patients with tubal pregnancy after laparoscopic salpingostomy. Study design: 480 tubal pregnancy patients were retrospectively stratified as mild, moderate, or severe group according to the new tubal classification system in which pelvic adhesions, tubal morphology, structure, and patency were included. The follow-up was performed for 24 months to determine spontaneous pregnancy outcomes. Results: The tubal classification was significantly associated with intrauterine pregnancy rates (mild 70.9% vs. moderate 66.0% vs. severe 41.8%, P = 0.001) and recurrent ectopic pregnancy rates (mild 2.8% vs. moderate 4.2% vs. severe 10.9%, P = 0.047). The 24-month cumulative rate of intrauterine pregnancy was 73.5% in the mild group, 68.5% in the moderate group, and 45.8% in the severe group ( P = 0.002). The 24-month cumulative repeat ectopic pregnancy rate was 6.6% in the mild group, 9.1% in the moderate group, and 15% in the severe group ( P = 0.154). In Cox multivariate regression analysis, a lack of a history of infertility [hazard ratio (HR) = 0.633, P = 0.001] and tubal scoring (mild HR = 2.408, P = 0.008; moderate HR = 2.147, P = 0.010) were significantly associated with a higher rate of spontaneous intrauterine pregnancy. Having a history of infertility (HR = 0.351, P = 0.037) and no prior abdominopelvic surgery (HR = 2.907, P = 0.014) were significantly associated with a lower ectopic pregnancy rate. Conclusion: The new tubal classification system significantly correlated with spontaneous pregnancy outcomes in patients with tubal pregnancy following laparoscopic salpingostomy.